Assessing COVID effects on farmers using a phone survey in the Feed the Future zone of influence in Bangladesh - Ahmed, Akhter; Bakhtiar, M. Mehrab; Abedin, Naveen; Ghostlaw, Julie (International Food Policy Research Institute, 2020)
The Bangladesh Policy Research and Strategy Support Program (PRSSP), implemented by the International Food Policy Research Institute (IFPRI), designed and conducted a telephone survey to capture the effects of COVID-19 on farmers during the first five months after the coronavirus outbreak began in Bangladesh. This report provides the survey’s findings, with particular attention to access to credit and assistance and supply chain disruptions (e.g., labor shortages, access to agricultural inputs, selling prices of outputs, etc.).